THE INFLUENCE OF ENTREPRENEURIAL KNOWLEDGE AND LOCUS OF CONTROL TO ENTREPRENEURIAL INTENTION: - - Tiktik Siti Jenab; Meta Arief (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to determine how the influence of entrepreneurial knowledge and locus of control on entrepreneurial intention. This is research is a correlational study with a quantitative approach.The subjects in this study were students of SMK MedikaCom Bandung which consisted of several skill programs with a tootal of 476 people. The sample ofthis study amoounted to 217 students of class XI. Data analysis in this study used SPSS 25. The result of this study indicate that entrepreneurial knowledge and locus of coontrol have an effect on entrepreneurial untention.